Isolation and evaluation the effect of Bacillus subtillis BLD01 strain on the survival rates and gut microbiota of Penaeus vannamei after challenge with Vibrio parahaemolyticus - Hoang Duc, Le; Trung Nam, Nguyen; Hoang Oanh, Dang Thi; Trung Thanh, Tran; Hoang Ha, Chu (Vietnam Journal of Biotechnology, 2022)
Acute hepatopancreatic necrosis disease (AHPND) caused by Vibrio parahaemolyticus has caused severe damage to the shrimp farming industry of Vietnam. Probiotics are chosen as a prophylactic method to mitigate the outbreak of diseases. We report in this article the isolation and evaluation of the effect of a potential probiotic, Bacillus subtilis BLD01, which enhances the survival rates and changes gut microbiota of whiteleg shrimp (Penaeus vannamei) after challenge with AHPND V. parahaemolyticus. After seven days of the challenge, the treatment where shrimps were fed with B. subtilis BLD01 strain (106 CFU/g) and challenge with AHPND V. parahaemolyticus (106 CFU/mL) showed high survival rates of 71% as compared to 33% in the treatment where shrimp were given standard feed without probiotics supplementation and challenged with AHPND V. parahaemolyticus. 16S rRNA amplicon data of the gut microbiomes of shrimps in four treatments were carried out using Illumina sequencing. A total of 231 436 reads were obtained, and a total of 14 phyla, 28 classes, 142 genera were revealed. The most abundant phyla in all subjects were Proteobacteria and Bacteroidetes. The sequence number of the Vibrio genus was the highest with 28% in treatment without B. subtillis BLD01 in-feed addition and shrimps challenged with AHPND V. parahaemolyticus. The sequence number of Bacillus genus was the highest with 3% in the treatment with B. subtillis BLD01 addition and without AHPND V. parahaemolyticus challenge. These results contribute to confirming the mechanism of action of B. subtilis against V. parahaemolyticus in the experimental model, creating a scientific basis for the development and use of probiotics products applied in shrimp farming in Vietnam.